Broken lines path following algorithm for a water-jet propulsion USV with disturbance uncertainties. (1st April 2020) - Zhao, Yujiao; Qi, Xin; Incecik, Atilla; Ma, Yong; Li, Zhixiong
Abstract: To fulfill autonomous navigation of unmanned surface vehicle, it is pivotal to resolve unmanned surface vehicle path following issue. However, the problem that we are concerned with is hindered by unmanned surface vehicle's nonlinearity and the disturbance uncertainties brought by the navigation environment. In this paper, we focus on path following problem for a jet driven underactuated unmanned surface vehicle. The stressed followed paths in practical application are broken lines connected by continuous straight lines rather than smooth lines. By calculating the virtual target on each straight line in following the unmanned surface vehicle dynamically, we propose a broken lines path following algorithm for the unmanned surface vehicle in an uncertain environment. By employing our unmanned surface vehicle experiment platform that we developed a series of numerical simulations and physical tests have been carried out. Results verify the superiority and effectiveness of our broken lines path following algorithm for unmanned surface vehicle especially in continuous broken lines following scenarios. Highlights: USV path following issue is solved using a new BLPFA method. Uncertainties and nonlinearities in the USV model is considered. Numerical simulations and physical tests have been carried out.